Evaluation of Perceived Environmental Risks of Residents’ Life under the Perspective of Environmental Public Opinion - Ye, Fengjiao; Wang, Xueru; Lin, Jun (Problemy Ekorozwoju, 2024)
Population health, social development and the environment are important elements of sustainable development. This article uses the China People’s Daily message board to collect environmental public opinion data, visualizes the public opinion hotspots of environmental based on word frequency statistics, and applies the Latent Dirichlet Allocations (LDA) topic model to analyze the spatial distribution of environmental risk perception dimensions. The conclusions are as follows: (1) in terms of the hotspots of environmental public opinion, the most frequent occurrences are the living environment, interest demands and noise pollution. (2) There is heterogeneity in the topic of environmental risk perception. The perception of pollution source types has the highest weight in environmental risk perception in the eastern, central, and western regions. Specifically, the types of pollution sources in the eastern that receive the most attention are garbage and noise pollution. In addition to paying attention to noise pollution, the central and western also have a higher perceived weight on the polluters. Residents in northeast are most concerned about changes in residents’ health and living environment quality. (3) From the perspective of environmental risk perception, health perception has the highest proportion in northeast, followed by the eastern, and finally the central and western. Proportion of perception of interest demands is highest in the central region, perception of residential environment quality is highest in the northeast region, perception of pollution source types is highest in the eastern, central, and western regions, and lowest in the northeast region. Finally, some practical and feasible policy recommendations were proposed for different regions.